2005
DOI: 10.1590/s0004-282x2005000200007
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone in secondarily progressive multiple sclerosis: a series of 18 patients

Abstract: Mitoxantrone hydrochloride (Novantrone®) is an anthracenedione that has been used as one of the latest in a long line of general immunosuppresive agents studied in multiple sclerosis (MS). We reviewed the clinical, laboratory, neuroimaging and echocardiography data of 18 patients from February 2001 to March 2004 out of a total number of 100 patients with definite MS. Fourteen patients were women (77.7%) and four were men. The mean age of the patients was 41.6±10 years old (confidence intervals 95%: 36.4-46.7 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Interestingly, the other twelve SPMS patients enrolled in the Montu study experienced a decrease in LVEF but MX was not discontinued since this decrease did not yield an LVEF less than 55% in any of these patients. 58 The patients were all monitored by ECHO and were on average younger (mean age = 41.6) than the patients in the current study. The EDSS scores of patients in the Montu study were not indicated.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Interestingly, the other twelve SPMS patients enrolled in the Montu study experienced a decrease in LVEF but MX was not discontinued since this decrease did not yield an LVEF less than 55% in any of these patients. 58 The patients were all monitored by ECHO and were on average younger (mean age = 41.6) than the patients in the current study. The EDSS scores of patients in the Montu study were not indicated.…”
Section: Discussionmentioning
confidence: 70%
“…The EDSS scores of patients in the Montu study were not indicated. 58 There are a number of factors that may have contributed to the lack of MX efficacy observed in our study. One EDSS-related limitation in this study, as well as other studies, was that all enrolled participants were grouped together regardless of EDSS score (range of 3.5-8).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This confirmed outcomes of previous studies. Here, MIX treatment did not provide a positive impact on MS progression [51,[56][57][58], which in particular appeared in progressive patients with superimposed relapses. Therefore, one can assume that MIX efficacy depends on the number of relapses experience by patients in the year before initiation of MIX treatment [59].…”
Section: Tca Treatment Versus Mitoxantrone Application In Two Similarmentioning
confidence: 99%